POLIGAMI TANPA IZIN ISTERI: PERSPEKTIF HUKUM ISLAM DAN POSITIF - Marpaung, Zaid Alfauza; Irham, Muhammad Iqbal; Zein, Achyar (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
The purpose of this article is to discuss the impact of polygamous marriages without the consent of the wife from the perspective of positive and Islamic law. Polygamy that is carried out secretly without the wife's permission or knowledge causes many disputes that disrupt household harmony and even lead to divorce. This is because the wife does not accept it, feels betrayed, and hurt. Indonesian marriage law basically adheres to the principle of monogamy. However, there are exceptions for men who can have more than one wife, with the condition of the wife's permission. The method used is normative legal research through a conceptual approach and legislation, whose data comes from primary, secondary and tertiary legal materials. The data is then collected and analyzed qualitatively. The results showed that polygamous marriages secretly without the knowledge and consent of the wife are unlawful. The legal consequences of such violations can be prosecuted criminally as stipulated in Article 279 of the Criminal Code and can be requested for annulment to the court. From the point of view of Islamic law, polygamous marriages are allowed in emergency situations that prioritize justice and the goal of benefit. If these conditions cannot be met and the marriage is detrimental to the household, then polygamy is haram.  Keywords: Marriage, Polygamy, Wife's Permission, Islamic Law, Positive Law